Structural diversity and adaptations in some Mediterranean evergreen sclerophyllous species - Christodoulakis, N.S. (Environmental and Experimental Botany, 1992)
Four evergreen sclerophyllous species were investigated morphologically and anatomically. Buds, leaves and roots from Ceratonia siliqua, Olea europaea, Pistacia lentiscus and Quercus coccifera were studied and compared for structural diversity. Analysis of the anatomical data suggested diverging features. The ecological equivalence of these species cannot be attributed to their structure. © 1992.
Keywords: Ceratonia siliqua; Greece, Athens; leaf structure; Olea europaea; Pistacia lentiscus; Quercus coccifera; sclerophylly